Challenges Enrolling Children Into Traumatic Brain Injury Trials: An Observational Study. (January 2017) - Stanley, Rachel M.; Johnson, Michael D.; Vance, Cheryl; Bajaj, Lalit; Babcock, Lynn; Atabaki, Shireen; Thomas, Danny; Simon, Harold K.; Cohen, Daniel M.; Rubacalva, Daniel; David Adelson, P.; Bulloch, Blake; et al.
Abstract: Objectives: In preparation for a clinical trial of therapeutic agents for children with moderate‐to‐severe blunt traumatic brain injuries (TBIs) in emergency departments (EDs), we conducted this feasibility study to (1) determine the number and clinical characteristics of eligible children, (2) determine the timing of patient and guardian arrival to the ED, and (3) describe the heterogeneity of TBIs on computed tomography (CT) scans. Methods: We conducted a prospective observational study at 16 EDs of children ≤ 18 years of age presenting with blunt head trauma and Glasgow Coma Scale scores of 3–12. We documented the number of potentially eligible patients, timing of patient and guardian arrival, patient demographics and clinical characteristics, severity of injuries, and cranial CT findings. Results: We enrolled 295 eligible children at the 16 sites over 6 consecutive months. Cardiac arrest and nonsurvivable injuries were the most common characteristics that would exclude patients from a future trial. Most children arrived within 2 hours of injury, but most guardians did not arrive until 2–3 hours after the injury. There was a substantial range in types of TBIs, with subdural hemorrhages being the most common. Conclusion: Enrolling children with moderate‐to‐severe TBI into time‐sensitive clinical trials will require large numbers of sites and meticulous preparation and coordination and will prove challenging to obtain informed consent given the timing of patient and guardian arrival. The Federal Exception from Informed Consent for Emergency Research will be an important consideration for enrolling these children.